The Application of Progressive Muscle Relaxation Therapy on Chronic Pain in the Elderly with Hypertension: A Case Study - Parulian Dormaida Gultom; Grech Sinaga (CV. AFDIFAL MAJU BERKAH, 2024)
Hypertension is a major health problem that is common in the elderly. The changes in the cardiovascular system due to increasing age are the cause of hypertension in the elderly which may cause many complications if not controlled properly. There are many kinds of treatment for hypertension; one of them is progressive muscle relaxation therapy. The purpose of this study was to treat chronic pain in elderly people with hypertension by applying progressive muscle relaxation therapy. This study used a descriptive method with a case study design of nursing care including assessment, diagnosis, intervention, implementation and evaluation. The respondent was an elderly with chronic hypertension pain and sleep pattern disturbance. The research showed that progressive muscle relaxation therapy has proven effective in reducing chronic hypertension pain in hypertensive client. Based on nursing actions carried out for 3 days, the application of progressive muscle relaxation therapy can be used as an adjunct to overcome chronic pain which is useful for reducing blood pressure in elderly people with hypertension. Meanwhile, sleep support by listening to music can be used as an intervention to elderly in order to divert pain and anxiety to feel comfort and relax